Differential effects of Kv7 (M‐) channels on synaptic integration in distinct subcellular compartments of rat hippocampal pyramidal neurons - Mala M. Shah; Michele Migliore; David A. Brown (2011)
The K(V)7/M-current is an important determinant of neuronal excitability and plays a critical role in modulating action potential firing. In this study, using a combination of electrophysiology and computational modelling, we show that these channels selectively influence peri-somatic but not dendritic post-synaptic excitatory synaptic potential (EPSP) integration in CA1 pyramidal cells. K(V)7/M-channels are highly concentrated in axons. However, the competing peptide, ankyrin G binding peptide (ABP) that disrupts axonal K(V)7/M-channel function, had little effect on somatic EPSP integration, suggesting that this effect was due to local somatic channels only. This interpretation was confirmed using computer simulations. Further, in accordance with the biophysical properties of the K(V)7/M-current, the effect of somatic K(V)7/M-channels on synaptic potential summation was dependent upon the neuronal membrane potential. Somatic K(V)7/M-channels thus affect EPSP-spike coupling by altering EPSP integration. Interestingly, disruption of axonal channels enhanced EPSP-spike coupling by lowering the action potential threshold. Hence, somatic and axonal K(V)7/M-channels influence EPSP-spike coupling via different mechanisms. This may be important for their relative contributions to physiological processes such as synaptic plasticity as well as patho-physiological conditions such as epilepsy.